2015
DOI: 10.4236/ijcm.2015.68074
|View full text |Cite
|
Sign up to set email alerts
|

Giant Coronary Artery Pseudoaneurysm after Drug-Eluting Stent Implantation

Abstract: Formation of coronary artery pseudoaneurysm after percutaneous coronary intervention is rarely reported. A close review of available literature indicates a trend of growing incidence in recent times. Here, we present a case of coronary pseudoaneurysm developing in the left circumflex artery within 50 days of sirolimus-eluting stent implantation in a 47-year-old man who was treated for triple-vessel coronary artery disease. Initially, the patient refused any further treatment. However, considering the rapid gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Using the PRISMA methodology, 36 articles 1‐36 were identified that fulfilled criteria of PSA after stenting in an atherosclerotic lesion in the absence of concomitant infection (Figure 2). With the addition of the present case report (please see below), there are 37 well‐documented and reported coronary PSA cases (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the PRISMA methodology, 36 articles 1‐36 were identified that fulfilled criteria of PSA after stenting in an atherosclerotic lesion in the absence of concomitant infection (Figure 2). With the addition of the present case report (please see below), there are 37 well‐documented and reported coronary PSA cases (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Pseudoaneurysm (PSA) formation is a rare but well‐known complication of coronary stenting 1‐36 . It develops after a perforation disrupts the integrity of the vessel wall but is contained by extravascular thrombosis, fibrosis, and pericardial constraint.…”
Section: Introductionmentioning
confidence: 99%